Through the labyrinths of Ethics: Creativity as a catalyst for ethical reflection in educational contexts - Valquaresma, Andreia (Farol, 2024)
In a changing world, the ethical challenges faced by contemporary society have become increasingly complex. In addition to geopolitical tensions, climate change and social issues raised by migration, it is also necessary to consider the impact of the technological revolution on social inequalities. In times of uncertainty, creativity is fundamental in the construction of innovative solutions and in the critical analysis of underlying ethical dilemmas, especially in educational contexts in which it is urgent to promote the personal and collective agency of educators, through ethical reflection. This article reflects on the importance of an ethical perspective on creativity and discusses psychological and educational strategies that can facilitate its exploration, with a view to building a more just and equitable society.